Effective Practices in Community Supervision model: Staff perceptions of the model and implementation - Gleicher, Lily (European journal of probation, 2020)
Staff who provide service to individuals under correctional supervision are critical to organizational change, implementation, and sustainability of policies and practices. The training on evidence-based practices demonstrates a movement toward effective interactions with community supervision officers and their clients, specifically to the Risk–Need–Responsivity model and core correctional practices. Research over the past several decades provides that fidelity to Risk–Need–Responsivity and core correctional practice can reduce recidivism among the community correctional population. However, the correctional field has a history of training staff, but limited success in implementing and sustaining these practices. The current qualitative study analyzes the feedback from 307 community supervision officers who responded to open-ended questions regarding the implementation of Effective Practices in Community Supervision model, a curriculum that incorporates the Risk–Need–Responsivity model and core correctional practices. Qualitative responses indicate key themes that help and hinder the implementation of evidence-based practices: individual attitudes and beliefs, organizational elements, and leadership.